Pertumbuhan Seedling Anggrek Tanah (Spathoglottis plicata Blume) in Vitro sebagai Respons terhadap Berbagai Komposisi Media MS: In Vitro Seedling Growth of Ground Orchid (Spathoglottis plicata Blume) as a Response to Various MS Media Compositions - Defiani, Made Ria; Ida Ayu Astarini; I Made Saka Wijaya; Ni Luh Putu Kayika Febryanti (Jurnal Hortikultura Indonesia, 2024)
Spathoglottis plicata Blume is a ground orchid which has high economic and aesthetic values. Its existence in natural habitat is classified as vulnerable. Propagation of this orchid in vitro can be done by seed germination and seedling growth, which require a suitable culture medium. Murashige and Skoog (MS) has been widely used for in vitro seed germination and seedling growth of various orchids. However, the concentration of salts in MS often needs to be adjusted for best results. This study aimed to investigate in vitro growth of S. plicata seedlings as a response to various MS modification media. Protocorms of 6 weeks after seed sowing were cultured on MS modification media, namely, ¼ MS, ½ MS, MS0, and MS with addition of NAA and BAP. Treatments were arranged in a completely randomized design with 10 replications, each of which consisted of one culture vessel containing 5 clumps of protocorms. After six months in the treatment media, it was found that MS0 was the best medium for in vitro seedling growth, showing the highest leaf numbers and number of seedlings. After 4 weeks ex vitro, 13% of plantlets survived when acclimatized in a plastic shade house using rice-husk charcoal medium.Keywords: BAP, NAA, acclimatization, protocorm